Muscular dystrophy-related hospitalizations among male pediatric patients in the United States. Issue 3 (September 2015) - Bell, Christopher F.; Kurosky, Samantha K.; Candrilli, Sean D.
Abstract: Objective . While the economic burden of muscular dystrophy (MD) has been well documented, little is known of specific costs associated with Duchenne muscular dystrophy (DMD), the most prevalent form of MD. This study assessed trends in MD-related hospitalizations and costs among young males, which may reflect utilization of the DMD population in the United States. Study design. A retrospective observational study of hospitalizations of males aged 0–20 years with a primary diagnosis code for MD was conducted using data from a weighted, nationally representative database of pediatric hospitalizations in the US. Rates, characteristics and cost of MD-related hospitalizations were compared to hospitalizations not related to MD. Results. The rate of MD-related hospitalizations increased by 9% between 2000 and 2006 and then decreased by 13% in 2009. The mean length of stay for discharges related to MD was approximately 9 days during each study year. The most frequent observed diagnoses (other than MD) and procedures were for respiratory-related complications. The mean total costs for MD-related discharges increased across the study period from 26, 785 in 2000 to 42, 751 in 2009. Conclusion . This study provides baseline and trend data describing hospitalizations of male pediatric patients with MD that may be used as baseline measurements for assessment of the impact of new strategies for managing the disease. Further assessment of the burden and the clinical, economic, and humanistic impacts of DMD is warranted.